1995
DOI: 10.1288/00005537-199512000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of intraoperative staging of the N0 neck in squamous cell carcinoma

Abstract: Management of the neck in squamous cell carcinoma of the upper aerodigestive tract continues to be a topic of great debate. One major problem is that incorrect clinical staging is expected in approximately 20% of necks. This is true of both clinical stage N0 and N+ necks, even when imaging studies are used. This prospective study of 108 necks in 79 patients examined the role of intraoperative palpation and inspection in improving the surgeon's ability to predict nodal stage. Of 62 patients with N0 necks clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
5

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 18 publications
2
54
0
5
Order By: Relevance
“…Consequently, many patients have to undergo a second surgical procedure to complete lymph node dissection after definitive pathologic assessment identifies microscopic metastatic disease not evident on intraoperative analysis. Our own work, and that reported by others, suggests that low sensitivity may also be an issue for intraoperative SLN analysis in SCCHN (18,21). Performing a second surgery on the neck is an undesirable scenario because this would likely increase complications and morbidity and could delay the use of adjuvant therapy.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Consequently, many patients have to undergo a second surgical procedure to complete lymph node dissection after definitive pathologic assessment identifies microscopic metastatic disease not evident on intraoperative analysis. Our own work, and that reported by others, suggests that low sensitivity may also be an issue for intraoperative SLN analysis in SCCHN (18,21). Performing a second surgery on the neck is an undesirable scenario because this would likely increase complications and morbidity and could delay the use of adjuvant therapy.…”
Section: Introductionmentioning
confidence: 64%
“…This technique has the potential to define those cN0 patients in whom neck dissection is most appropriate (i.e., those who are pathologically node positive), thereby obviating END and its associated morbidities in nodenegative patients. Numerous single-institution studies have suggested that SLN mapping in SCCHN accurately predicts the status of the neck (5,(17)(18)(19)(20)(21), and this finding is currently being evaluated in a large multicenter validation trial sponsored by the American College of Surgeons Oncology Group (ACOSOG Z0360 trial). When combined with intraoperative analysis of the SLN(s), this approach could allow for definitive staging and surgical treatment in a single procedure.…”
Section: Introductionmentioning
confidence: 99%
“…less than 4mm in primary tumor of the tongue), and favorable histologic differentiation [41,135]. They proposed a reliance on the radiological evaluation of the neck to take decision on the extent of treatment [55] and emphasized on the importance of frozen section as a guide on whether or not to proceed to neck dissection [122].…”
Section: Introductionmentioning
confidence: 99%
“…Use of radiological means like ultrsonography and CT scan has not contributed much to improvement in the staging [24,25]. Even the intra operative assessment has been found to be [26,27]. New imaging methods like PET-CT scan is not sensitive enough to modify the indication of elective neck dissection [28].…”
Section: Discussionmentioning
confidence: 99%